The Brazilian Tyres Case: Trade Supersedes Health. - Lavranos, Nikolaos (NLUJ, 2009)
The recent WTO Appellate Body decision in Brazil – Retreaded Tyres raises several interesting institutional and substantive issues. Institutionally, it starkly illustrates the inherent tension and potential for conflict that exists between regional dispute settlement systems and the WTO dispute settlement mechanism. In showing remarkably little deference towards the earlier decision of the MERCOSUR Arbitral Tribunal on the same issue, the Appellate Body essentially espouses a regime of supremacy – of WTO law over regional dispute settlement bodies, and of jurisprudence generated by WTO appellate bodies over jurisprudence generated by WTO panels. This attitude appears to be unsustainable in the light of the increasing proliferation of international courts and tribunals and the inevitable consequence of disputes being adjudicated by different courts and tribunals at various levels. Substantively, the dispute is a prime example of the difficulties of balancing non-trade interests and trade interests, with the latter prevailing. However, the Appellate Body’s narrow application of Article XX of GATT leaves WTO members such as Brazil insufficient room to address legitimate, urgent environmental and health problems through restrictions on trade.
Keywords: World Trade Organization (WTO); Appellate Body; Brazil – Retreaded Tyres case; MERCOSUR Arbitral Tribunal; Regional dispute settlement; International trade law; GATT Article XX; Environmental protection; Public health; Trade and environment; Non-trade concerns; Jurisprudence and hierarchy; Institutional conflict; Supremacy of WTO law; International adjudication; Overlapping jurisdictions; Sustainable development and trade